Prototype Box Breathing Innovation Overcoming the Risk of High Blood Pressure for Pregnant Women - Aprina, Aprina; Astuti, Titi; Anita, Anita (Buletin Penelitian Kesehatan, 2024)
Introduction: Hypertension during pregnancy is a common complication that increases the risk of preeclampsia, leading to maternal and fetal morbidity and mortality. Box breathing techniques have shown promise in lowering blood pressure and stress, but their effectiveness in pregnant women at risk of hypertension and preeclampsia has not been widely studied. This study aims to evaluate the efficacy of a prototype box breathing intervention in reducing blood pressure and symptoms in pregnant women at risk of these conditions. Methods: A quantitative, experimental study with a pretest-posttest design was conducted at four hospitals in Indonesia. A sample of 198 pregnant women in their 1st-3rd trimesters was selected using purposive sampling. The intervention involved the use of a prototype box breathing device, and data were collected on blood pressure and symptoms before and after the intervention. Data analysis was performed using the Wilcoxon test. Results: After the prototype box breathing intervention, there was a significant decrease in systolic blood pressure from 147.83 mmHg to 132.36 mmHg and diastolic blood pressure from 94.76 mmHg to 86.16 mmHg (p-value 0.000). The average symptom score also decreased from 5.93 to 1.25 following the intervention. Conclusion: The use of the prototype box breathing device is effective in lowering blood pressure and reducing symptoms associated with preeclampsia risk in pregnant women. This non-pharmacological intervention offers a promising approach for managing hypertension during pregnancy and preventing the progression to preeclampsia. Further research is needed to validate these findings and optimize the implementation of box breathing techniques in prenatal care.